P270 A global consensus on the definitions, diagnosis and management of fibrostenosing small bowel Crohn's disease. (30th January 2023) - Bettenworth, D; Baker, M E; Bemelmann, W; Bruining, D; D'Haens, G; D'Hoore, A; Dignass, A; Dotan, I; Feagan, B G; Feakins, R; Fleshner, P; Fletcher, J G; et al.
Abstract: Background: Small bowel fibrostenotic strictures are common in patients with Crohn's disease (CD). No global consensus recommendations on definitions, diagnosis and clinical management are available. Methods: Several systematic reviews followed by a RAND/University of California Los Angeles appropriateness study on the definitions, diagnosis and clinical management of fibrostenosing CD in clinical practice were performed. A panel of 28 global experts and a patient representative were convened. They assessed a total of 152 candidate items. The items were subsequently evaluated for appropriateness. Results: No accurate predictive biomarkers are available for naïve or anastomotic fibrostenosing strictures. Accurate diagnosis of fibrostenosing CD requires cross-sectional imaging which should evaluate bowel wall thickness, luminal narrowing and prestenotic dilatation. A potential inflammatory component should be assessed. Abdominal cross-sectional imaging was considered necessary prior to any treatment decision. The panel proposed an approach to medical, endoscopic, and surgical therapies (Figure 1 and Table 1). Technical characteristics for endoscopic balloon dilation and follow up strategies after successful dilation therapy were identified. Appropriateness, types and performance of different surgical approaches in various settings were evaluated. Conclusion: This global consensus provides clinical guidance for the diagnostic and therapeutic management of patients with fibrostenotic CD.